2020
DOI: 10.4274/jcrpe.galenos.2019.2019.0060
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with Depot Leuprolide Acetate in Girls with Idiopathic Precocious Puberty: What Parameter should be Used in Deciding on the Initial Dose?

Abstract: Doses of gonadotropin releasing hormone (GnRH) analogues used to treat idiopathic central precocious puberty (iCPP) vary among clinicians. Study aims were to evaluate the efficacy of a monthly 3.75 mg dose of leuprolide acetate (LA) to suppress the hypothalamo-pituitary-gonadal (HPG) axis in girls with iCPP and to determine factors that may have an impact on the supressing dose. Methods: Study subjects were 220 girls receiving LA for iCPP. LA was started at a dose of 3.75 mg/28 days. Suppression was assessed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…ICPP and EP were diagnosed based on the presence of secondary sexual characteristics [ 30 ], including BA greater than the chronological age (CA) [ 30 ] and peak luteinizing hormone (LH) levels > 5 IU/L according to a standard intravenous GnRH stimulation test [ 4 ], and the absence of central nervous system lesions on brain magnetic resonance imaging [ 4 ]. GnRHa was administered intramuscularly every 28 days, as a depot formulation of the GnRH analog leuprorelin, at a dose of 0.2–0.3 mg/kg/dose every 4 weeks [ 4 ]. GnRHa treatment was initiated before the age of 8 years (ICPP, range: 6.17–7.92) and between 8 and 9 years (EP, range: 8.00–8.92).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…ICPP and EP were diagnosed based on the presence of secondary sexual characteristics [ 30 ], including BA greater than the chronological age (CA) [ 30 ] and peak luteinizing hormone (LH) levels > 5 IU/L according to a standard intravenous GnRH stimulation test [ 4 ], and the absence of central nervous system lesions on brain magnetic resonance imaging [ 4 ]. GnRHa was administered intramuscularly every 28 days, as a depot formulation of the GnRH analog leuprorelin, at a dose of 0.2–0.3 mg/kg/dose every 4 weeks [ 4 ]. GnRHa treatment was initiated before the age of 8 years (ICPP, range: 6.17–7.92) and between 8 and 9 years (EP, range: 8.00–8.92).…”
Section: Methodsmentioning
confidence: 99%
“…This condition limits the final adult height owing to rapid growth velocity and early epiphyseal closure [ 3 ]. GnRH agonist (GnRHa) therapy is considered the standard treatment for this condition [ 4 ]. CPP treatment aims to delay the early progression of puberty, inhibit epiphyseal growth to prevent shorter adult height, and to allow normal sexual maturation to reduce psychosocial problems [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Doses of GnRHa for optimal HPG suppression are not well defined and they vary in different countries. Lower doses (3.75 mg/28 days, 80-120 µ/kg/28 days) are preferred in Europe and Asia, whereas in the US doses are higher (7.5-15 mg/ 28 days, 200-300 µ/kg/28 days) (43). A Japanese study concluded that the minimum effective suppressive dose is already 30 µg/kg (44).…”
Section: Discussionmentioning
confidence: 99%
“…A Japanese study concluded that the minimum effective suppressive dose is already 30 µg/kg (44). A Turkish study suggests that higher doses may be required for cases at advanced stages and increased body weight (>36.2kg) or BMI (>1.64 SDS) (43). Of note, the concerns of over suppression are suppression of growth, a possible transient…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of sexual development disorders in children, especially precocious puberty, has increased significantly in recent years and has become one of the most common pediatric endocrine diseases [9,10], and idiopathic central precocious (idiopathic central precocious puberty, ICPP) is especially important. The direct cause of ICPP is early initiation of the GnRH secretion pulse in the hypothalamus and the increase of the overall level, which activates the pituitary and downstream gonadal organs such as the ovaries and uterus, and makes the HPG axis reach the puberty state prematurely [11,12]. However, the mechanism underlying the abnormal increase in GnRH secretion requires elucidation and is the subject of current research.…”
Section: Discussionmentioning
confidence: 99%